2012
DOI: 10.1111/j.1460-2695.2012.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Some factors exerting an influence on the coaxing effect of austenitic stainless steels

Abstract: The present paper describes some factors exerting an influence on the coaxing effect of austenitic stainless steels. Particularly, the influence of prestrain was investigated in detail. The materials used were austenitic stainless steels, type 304 and 316. Type 304N2 was also used to examine the properties of the stabilized austenitic phase in type 304. Two types of rotating bending fatigue tests, i.e. the conventional constant amplitude tests and stress‐incremental tests, were performed using the specimens su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…In the strengthening region, the residual fatigue strength firstly increased and then decreased with the increasing of consumed life fraction under the previous loading. Generally, the coaxing effect was attributed to the work hardening due to the increase of dislocation density regardless of the preloading level . As can be seen in Figure B, the residual fatigue strength would be weakened when the previously consumed life fraction exceeded a specific value in the strengthening region.…”
Section: Nonlinear Damage Accumulation Modelsmentioning
confidence: 91%
“…In the strengthening region, the residual fatigue strength firstly increased and then decreased with the increasing of consumed life fraction under the previous loading. Generally, the coaxing effect was attributed to the work hardening due to the increase of dislocation density regardless of the preloading level . As can be seen in Figure B, the residual fatigue strength would be weakened when the previously consumed life fraction exceeded a specific value in the strengthening region.…”
Section: Nonlinear Damage Accumulation Modelsmentioning
confidence: 91%
“…However, the underlying mechanism of the coaxing effect has not been elucidated yet. It has been reported that the coaxing effect appears when work hardening 11) or strain-age hardening of carbon 12,13) are significant during fatigue. The latter factor likely plays an important role in the appearance of the coaxing effect in ferritic steels.…”
Section: Intrinsic Factors That Trigger the Coaxing Effect In Binary mentioning
confidence: 99%
“…21) Note that the coaxing effect in most cases has been found in metallic materials where strain age hardening occurs significantly, 22) except for austenitic stainless steels. 23,24) More specifically, the coaxing effect in carbon steels is considered to stem from non-propagating fatigue crack phenomenon associated with strain age hardening. Hence, many researches [24][25][26][27][28] have studied the small fatigue cracking behavior to understand the coaxing effect in the crack propagation portion of fatigue lives.…”
Section: Fatigue Testingmentioning
confidence: 99%